Strategi Komunikasi Marketing Public Relations dalam Membangun Brand Image (Studi: Communion Coffee) - Thalia Maisiedavita Siregar; Lina Sinatra Wijaya (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study aims to examine how public relations marketing communication strategies influence the brand image of Communion Coffee. A mixed-method approach was employed, combining qualitative and quantitative techniques. The qualitative approach was carried out through interviews to explore the implementation of push and pull strategies and how consumers perceived these, while the quantitative approach utilized questionnaires to measure the brand image formed in consumers’ minds. The findings indicate that push strategies—such as direct promotion, product bundling, customer service, and events—and pull strategies through Instagram management with consistent and engaging content contribute to shaping the brand image. Word-of-mouth emerged as the most effective channel compared to official social media, highlighting the need for further optimization of digital strategies. The study concludes that Communion Coffee’s PR strategies effectively establish its brand image as a cozy, homie, and vintage-style coffee shop, while recommending greater consistency in social media management and organizing creative events to strengthen brand positioning in the increasingly competitive coffee industry.